Prediction Of Mortality By Pediatric Risk Of Mortality (PRISM) III Score In NGMC Pediatric Intensive Care Unit - Bora, Roma (Journal of Nepalgunj Medical College, 2019)
Background: The pediatric risk of mortality (PRISM) III score helps in predicting prognosis. It is being used in most of the pediatric intensive care units of developed world and few of developing ones. We have undertaken this study to evaluate efficacy of PRISM III score in prediction of mortality.Material and Methods: Prospective hospital based analytical study conducted from May 2018 to April 2019 in patients admitted to pediatric intensive care unit (PICU) of NGMC, Nepal. The pediatric risk of mortality score (PRISM) III which includes 14 parameters (physiological and laboratory) was recorded within 24 hours of admission. A total of 480 patients were included. The final outcome was recorded as death or discharge.Result: It was observed that mortality increased with increasing PRISM III score approaching almost 100% by PRISM III score of 25 and more. The variables that were found to be risk factors for death were readmission, diseases of hepatobiliary system, mechanical ventilation (MV) and use of vasoactive drugs with p value of